Pengaruh Konten Sosial Media Instagram Mpr Ri Terhadap Online Angegament: Survei Pada Followers Akun Istagram @Mprgoid - Muhammad Iqbal Nana Supriatna; Daniel Handoko (Institut Nalanda, 2024)
This research examines the impact of Instagram social media content of the People's Consultative Assembly of the Republic of Indonesia (MPR RI) on online engagement of its followers. In the digital era, government agencies increasingly rely on social media to communicate with the public. The aim of this research is to analyze the effectiveness of the MPR RI's Instagram content strategy in increasing community interaction and participation online. The aim of this research is to measure the influence of Mpr Ri's Instagram social media content on online engagement, then the theories used are Instagram (miles 2019: 125) and online Engagemnet (Corkum et al 2021). And this research method uses quantitative survey data collection techniques and then distributes questionnaires to followers of the Instagram account @mprgoid as many as 75 respondents. content analysis and measurement of engagement metrics such as number of likes, comments & shares